The Effect of Reciprocal Teaching Learning Model Assisted by Flipbook on Critical Thinking Ability - Nurropidah, Reza; Puad, Mohd Hazwan Mohd (Sekolah Pascasarjana Universitas Negeri Malang (UM), 2025)
This study aims to determine the effect of the reciprocal teaching learning model assisted by Flipbook on students' critical thinking skills. The research method used was quasi-experimental. We conducted research on two classes: the experimental class and the control class. We conducted our research activities at Elementary School Biyawak in Majalengka Regency. The total population studied was 58 students, divided into two groups: the experimental class totaling 30 people and the control class totaling 28 people, with the sampling technique used being non-probability sampling with a purposive sampling approach. We collected the research data using a pretest and posttest with questions describing critical thinking ability. The findings of the study indicated that the reciprocal teaching model assisted by flipbook can significantly improve students' critical thinking skills based on the results of pretest and posttest data from 50.28 to 74.03 with a significance level of